Investigational Management for a Positive NIPT Result - Case Report - Elena Evelina STOICA; Laurentiu Camil BOHILTEA; Delia-Maria Gradinaru-FOMETESCU; Monica Mihaela CIRSTOIU (Modern Medicine)
Non-invasive prenatal testing (NIPT), since its introduction in 2011, has revolutionized prenatal screening, becoming widely used globally and replacing traditional screening methods in developed countries. The accuracy of NIPT in detecting aneuploidies is extremely high and there has been a recent trend towards improving NIPT for detecting microdeletion and microduplication syndromes, monogenic diseases, fetal sex determination, and RH genotyping. Significant progress has been made in molecular analysis techniques of fetal DNA, including methods such as massively parallel sequencing, RNA-based testing, digital PCR, and single nucleotide polymorphism analysis. We present the case of a 32-year-old patient who, at 12 weeks of gestation, had a non-invasive prenatal test result showing a maternal 22q11.2 deletion. Following genetic consultation, further investigations were conducted to stratify the fetal risk of inheriting the microdeletion syndrome. As a result, microarray CGH cytoarray from amniotic fluid was performed, and no 22q11.2 deletion was detected. In this case, complete elucidation of the origin of the deletion found in NIPT could not be achieved, as it would require arrayCGH testing for the mother, a test that was not performed due to financial reasons. Given the high rate of genetic syndromes with potential impact on fetal development and familial psychological impact, we wish to emphasize the necessity of financial support from the state to introduce non-invasive prenatal testing into the list of reimbursed analyses covered by health insurance. This would enable superior testing and, implicitly, genetic prevention of all pregnancies, facilitating appropriate risk stratification of pregnancies in our country.